Time-Restricted Eating for 12 Weeks Does Not Adversely Alter Bone Turnover in Overweight Adults - Lobene, Andrea J. (Nutrients, 2021)
Weight loss is a major focus of research and public health efforts. Time-restricted eating (TRE) is shown to be effective for weight loss, but the impact on bone is unclear. Short-term TRE studies show no effect on bone mineral density (BMD), but no study has measured bone turnover markers. This secondary analysis examined the effect of 12 weeks of TRE vs. unrestricted eating on bone turnover and BMD. Overweight and obese adults aged 18–65 y (n = 20) were randomized to TRE (ad libitum 8-h eating window) or non-TRE. Serum N-terminal propeptide of type I collagen (P1NP), cross-linked N-telopeptide of type I collagen (NTX), and parathyroid hormone (PTH) levels were measured and dual-energy X-ray absorptiometry (DXA) scans were taken pre- and post-intervention. In both groups, P1NP decreased significantly (p = 0.04) but trended to a greater decrease in the non-TRE group (p = 0.07). The treatment time interaction for bone mineral content (BMC) was significant (p = 0.02), such that BMC increased in the TRE group and decreased in the non-TRE group. Change in P1NP was inversely correlated with change in weight (p = 0.04) overall, but not within each group. These findings suggest that TRE does not adversely affect bone over a moderate timeframe. Further research should examine the long-term effects of TRE on bone.